MS EXCEL UTILISATION WITH DIFFERENTIAL EQUATIONS APPLICATIONS - VAGASKA, Alena (Trends in education, 2008)
The contribution presents the possibilities of MS Excel application to mathematics education at technical universities, specifically to applicable tasks related to the theory of differential equations.
Keywords: differential equations; applications; numerical mathematics; MS Excel